2018
DOI: 10.1016/j.ejor.2017.05.040
|View full text |Cite
|
Sign up to set email alerts
|

MIP approaches for the integrated berth allocation and quay crane assignment and scheduling problem

Abstract: In this paper we consider an integrated berth allocation and quay crane assignment and scheduling problem motivated by a real case where a heterogeneous set of cranes is considered. A first mathematical model based on the relative position formulation (RPF) for the berth allocation aspects is presented. Then, a new model is introduced to avoid the big-M constraints included in the RPF. This model results from a discretization of the time and space variables. For the new discretized model several enhancements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(47 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…Correcher et al [24] focused on the berth allocation problem and the quay crane assignment problem in an integrated way, and proposed a new mixed integer linear model to solve. Agra et al [25] investigated an integrated berth allocation, quay crane assignment, and scheduling problem in which a heterogeneous set of cranes was considered, and a rolling horizon metaheuristic was introduced to solve hard instances. Moreover, the uncertainty in vessel arrival times and quay crane handling rates was considered, and the recoverable robustness was introduced for the weekly berth and quay crane planning problem by Iris et al [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Correcher et al [24] focused on the berth allocation problem and the quay crane assignment problem in an integrated way, and proposed a new mixed integer linear model to solve. Agra et al [25] investigated an integrated berth allocation, quay crane assignment, and scheduling problem in which a heterogeneous set of cranes was considered, and a rolling horizon metaheuristic was introduced to solve hard instances. Moreover, the uncertainty in vessel arrival times and quay crane handling rates was considered, and the recoverable robustness was introduced for the weekly berth and quay crane planning problem by Iris et al [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that the integration approach might be efficient in different cases. Recently, Agra and Oliveira (2018) studied the integrated berth allocation, quay crane assignment and scheduling problem motivated by a real case where a heterogeneous set of cranes was considered. They proposed a MIP model based on the relative position formulation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, a significant focus has been given to the integrated berth allocation and crane assignment problem for container terminals (e.g. Agra & Oliveira, 2018;Vacca et al, 2013). However, few works exist dealing with the case of bulk ports.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the recent advances in this research area, in 2017, Wu and Ma [10] focused on the problem of scheduling quay cranes, by considering the draft and trim constraints, with the goal of minimizing loading time. In 2018, Agra and Oliveira [11] presented an integrated model of berth allocation, quay crane assignment and scheduling problem, considering a set of heterogeneous cranes with discretion for time and space variables. The efficient operation of the terminal depends on the proper planning of the container movement, called "stowage planning".…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%